Acute caffeine ingestion results in increased vastus medialis muscle activation and improved muscle performance during short-term high intensity isokinetic exercise in trained men - Duncan, M.; Thake, C. D.; Downs, P. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
It is well established that acute caffeine ingestion enhances endurance performance in humans (Graham, 2001). However, the effect of caffeine on muscle strength performance has been less thoroughly examined and studies examining this issue have yielded equivocal findings (Astorino and Roberson, 2010). Some data suggest direct effects on muscle excitation-contraction coupling and motor unit recruitment, which are independent from those related to metabolic efficiency (Walton et al., 2003; Tarnopolsky and Cupido, 2000). These studies have focused on maximal isometric strength, whereas the effect of caffeine on neuromuscular function during dynamic contractions at different speeds has not been investigated thoroughly (Bazzuchi et al. 2001), thus limiting the conclusions that can be made across the torque-velocity relationship. The aim of this study was to examine the effect of caffeine ingestion on muscle torque production and muscle activity at different contraction speeds in trained men. Following ethics approval and informed consent, 10 strength trained males (Mean age ± SD = 22 ±1.1 years) volunteered to participate. A double-blind, randomised cross over design was used. Sixty minutes post ingestion of caffeine (6mg kg-1) or placebo diluted into 250ml artificially sweetened water, participants completed 6 repetitions of dominant knee extension on an isokinetic dynamometer (Cybex Norm, CSMi Solutions, Massachusetts, USA) at 3 angular velocities (30°sec, 150°sec, 300°sec, conducted in ascending order) with one minute rest between sets. Average torque for the knee extensors and electromyographical (EMG) activity of the vastus medialis were assessed at each velocity. Root mean square (RMS) EMG activity was normalised against a maximal voluntary isometric contraction at an angle of 15 degrees knee extension, established during habituation sessions. Results from repeated measures ANOVA indicated that muscle torque production was significantly higher (p=0.02) with caffeine (91.1±11.6nm) compared to placebo (84.5±12nm) and that muscle torque decreased as contraction speed increased (p=0.001). Mean torque ± SD was: 116.6±17.4nm, 86.2±9.9nm and 61.2±8.5nm for velocities of 30°sec, 150°sec, 300°sec respectively. A significant (p=0.02) substance by velocity interaction for muscle activity indicated significantly higher muscle activity in the presence of caffeine vs. placebo and that this difference was amplified as angular velocity increased (See Figure 1). Thus, this study demonstrates that acute caffeine ingestion improves muscle performance during short-duration maximal dynamic contractions. The concomitant increase in muscle activity also supports the hypothesis of an effect of caffeine on motor unit recruitment during, brief, high-intensity resistance exercise.